Juridical Study on the Law of Proof of Witchcraft in Criminal Law Reform in Indonesia - Suparno (STIE AAS Surakarta, 2021)
The community continues to develop very dynamically related to rules or laws that must always be updated or new laws are created, or the existence of a community culture that has existed for a long time but has not been legalized in the form of written law. Indonesia is a country that is famous for its diverse culture, spiritual life in Indonesia is very thick, making people in some areas have faith or even the ability to see things that are supernatural or learn magic where one of them is witchcraft. For protection and legal certainty relating to the crime of witchcraft among the public, and preventing the occurrence of vigilante actions against someone accused of being a witch, it is necessary to have a criminal law policy against the crime of witchcraft and a criminal law policy has an important role because the Criminal Code we adopted from Dutch colonialism did not regulate the problem of witchcraft. The purpose of this research is to find out about the concept of witchcraft offenses according to positive law in Indonesia and to find out the Law of Proving the crime of witchcraft in the Criminal Law Reform in Indonesia. The research method used in this study is a normative legal research method or also referred to as doctrinal legal research which is sourced from library law materials. Thus, it is undeniable that regulations governing this issue are indispensable for law enforcement in Indonesia, because so far there have been many victims. The debates that have been going on so far have mostly led to proof, while witchcraft has not been proven because it is still difficult to accept logically